Tra i più anziani cultori di Freud: Massimo Fagioli alla SPI (1964-1976) - Iacarella, Andreas (Il sogno della farfalla, 2022)
Drawing from new archival documents, this article provides a reconstruction of Massimo Fagioli’s human and professional path during his years as member of the Psychoanalytic Society. The documents revealed an active participation to the Society, particularly after the publication of Death instinct and knowledge. He tenaciously contributed to the society work: on one hand by attempting a collective society reform and opening to new ideas and on the other, with the aim to defend his original theory.